Pengaruh Penggunaan Aerosil Terhadap Disolusi Tablet Isoniazid (Inh) Cetak Langsung - Syofyan Syofyan; Thika Dwi Lestari; Rieke Azhar (Jurnal Farmasi Higea, 2014)
The research about the effect of aerosil to the dissolution rate of isoniazid tablet with direct compression method has been done. Isoniazid tablets were made with different aerosil consentration in each formulas, that is 0.5%; 1%; 1.5%. Tablet evaluation were done by measuring drug loading assay and dissolution test using HCl 0.1 N. The assay was measured using spectrophotometer UV at 266.5nm; where obtained levels of isoniazid tablets in each formulas is 95.779% - 103.776%. The results of disolution test showed that every formulas reached the 80% of cumulatif persentage as follows, 98.671%; 98.441%; 98.327% at 45th minutes. The result concluded that the addition of execessive aerosil as lubricant can decreased tablet disintegration rate and dissolution rate.